EFEKTIVITAS KERJA PEGAWAI PT ANGKASA PURA II (PERSERO) TANJUNGPINANG (Studi Pada Divisi Kepegawaian dan Umum) - edward mandala; neng suryanti nengsih; kurnia (JURNAL ILMU SOSIAL DAN ILMU POLITIK, 2021)
In research on the Work Effectiveness of PT Angkasa Pura II (Persero) Tanjungpinang Employees (Studies in the Personnel and General Division), several symptoms of the problem were found including the lack of effective supervision from the leadership of PT Angkasa Pura II (PERSERO) Tanjungpinang, problems related to human resources including the level of discipline. , where almost every day there are employees who are late but also leave the workplace early or are absent and others. The purpose of this study was to determine the Work Effectiveness of the Employees of PT Angkasa Pura II (Persero) Tanjungpinang (Studies in the Division of Personnel and General). The total population in this study amounted to 491 people and the sample in this study was 148 people with the exception of the Head of Administration and Commercial Division Manager of PT Angkasa Pura II Tanjungpinang who was made the key informant. Researchers used purposive sampling technique. The data analysis technique that the writer uses is descriptive qualitative. The results of interviews and direct observations indicate that the Work Effectiveness of the Employees of PT Angkasa Pura II (Persero) Tanjungpinang (Study in the Personnel and General Division) can be categorized as running effectively in accordance with the duties and functions of PT Angkasa Pura II (Persero) Tanjungpinang.